Kejelasan Sasaran Anggaran, Sistem Pengendalian Akuntansi, dan Kinerja Manajerial: Studi Empiris pada Pemerintah Daerah Kabupaten dan Kota Se-Propinsi DIY - Emile Satia Darma; Abdul Halim (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
This research is to examine the effects of the budget goal clarity and accounting control system on managerial performances of the local governments. This research is conducted on a cross-sectional basis. Analysis of this research is conducted on 271 respondents, who are structural (echelon) officials of the regencies and municipal governments of the Province of Yogyakarta Special Territory. Samples of those officials are composed of service/authority/office managers/heads, department/sector/ subservice managers, subdepartment/subsector/section managers. Results of data analysis (using regression method) showing the variables of the budget goal clarity and accounting control system affect positively significant (p0.01) on the increase of managerial performance. Further researches may be conducted by reducing those limitations in this research. Within the scope of contingency model there are still a lot of contextual factors or other contingent variables that can be hypothesized to interact the effects of the control design of performance. This is useful to find the fittest model in the control design and contextual factors in a particular organization. Different organizations have different control design and contextual factors as well.